Causes of Academic Underachievement at Schools Run by Yatta Education Directorate from Teachers' Point view - Bheis, Jamal Mohammed; Katalo, Khaled Sulaiman (Journal of Educational and Psychological Sciences, 2022)
The present study aims at recognizing the reasons behind academic underachievement at schools Run by Yatta education directorate from teachers' point. For the sake of the study, the researcher has developed a questionnaire consisting of 62 articles including five factors, learners, parents, teachers, education system and textbooks. The study sample includes 118 teachers, principals and supervisors. As for analysis, the data is analyzed using SPSS. The descriptive analytical method was used in the study.Results show that academic underachievement refers to five factors; students unawareness to the importance of learning, students ignorance to fulfill school assignments, parents unawareness to follow up their children achievements, teachers unawareness to students' abilities and preferences, overcrowding classrooms and the increasing numbers of new students joining the basic level are other causes due to the national system of education. Moreover, complexity of textbooks which seems higher in level than learners'. Consequently, the researcher concludes to the following; (i) revising the automatic promotion because of its learning problems in the following levels, (ii) reducing the number of learners in classrooms through establishing new schools, (iii) improving learners' skills and advising them about best learning times and (iv) arousing parents awareness to properly fulfill their children needs.
Keywords: Educational Tetardation; Yatta Education Directorate